DETERMINAN PENGGUNAAN ALAT KONTRASEPSI TRADISIONAL DI JAWA TIMUR - Mursyidul Ibad; Indah Lutfiya; Ali Imron; Mardiyono Mardiyono (Universitas Fort De Kock, 2021)
Abstract: Determinant of Traditional Contraceptive Use in East Java. The 2002-2017 IDHS data showed an increasing percentage of traditional contraceptive users in Indonesia, including in East Java from 2.8% to 6.7%. This study aimed to analyze the determinants of traditional contraceptive use in East Java. This study was a non-randomized study with cross sectional design using 2017 IDHS secondary data. The sample study was 5,583 married reproductive age women aged 19-49 years from the 2017 IDHS data of East Java. Data were analyzed by multiple logistic regression. The determinant factors of traditional contraceptive use in 2017 IDHS data of East Java were Method Information Index (p = 0,000), age of woman (p = 0,025), education (p = 0,000), place of residence (0,004), knowledge of woman’s fertile period (p = 0,006), and information from TV (p = 0.005). While information from radio (0.142) was not related to the use of traditional contraceptives. A policy on the use of modern contraceptives is needed, which is targeted and focused on women of childbearing age married with a higher education background in urban areas. Optimizing the role of family planning counselors to increase family planning knowledge is very important in increasing the use of modern contraceptives in East Java. Keywords: determinant, traditional contraceptive, married reproductive age women Abstrak: Determinan Penggunaan Alat Kontrasepsi Tradisional di Jawa Timur. Data SDKI 2002-2017 menunjukkan peningkatan persentase pengguna alat kontrasepsi tradisional di Indonesia, termasuk di Jawa Timur dari 2,8% menjadi 6,7%. Penelitian ini bertujuan menganalisis faktor determinan penggunaan alat kontrasepsi tradisional di Jawa Timur. Penelitian ini merupakan penelitian nonreaksional dengan desain cross-sectional menggunakan data sekunder SDKI 2017. Sampel penelitian 5.583 WUS kawin 19-49 tahun dari data SDKI Jawa Timur 2017. Data dianalisis dengan regresi logistik ganda. Faktor determinan penggunaan alat kontrasepsi tradisional di Jawa Timur 2017 diantaranya Method Information Index (p=0,000), umur wanita (p=0,025), pendidikan (p=0,000), tempat tinggal (0,004), pengetahuan masa subur (p=0,006), dan sumber informasi TV (p=0,005). Sedangkan informasi dari radio (0,142) tidak berhubungan dengan penggunaan alat kontrasepsi tradisional. Diperlukan kebijakan penggunaan alat kontrasepsi modern yang lebih tepat sasaran dan memfokuskan pada WUS kawin dengan latar pendidikan tinggi di perkotaan. Optimalisasi peran PKB untuk meningkatkan pengetahuan KB sangat penting dalam peningkatan penggunaan alat kontrasepsi modern di Jawa Timur. Kata kunci: determinan, alat kontrasepsi tradisional, WUS kawin